The Influence of Substrate, Binder, and Additives on Suspension Coating Properties at Elevated Temperatures - Sergey N. Grigoriev; Yaroslav R. Meleshkin; Nestor Washington Solís Pinargote; Anton Smirnov; Maksim V. Prozhega; Egor O. Konstantinov; Vadim V. Korovushkin; Maksim I. Prudnikov; Marina A. Volosova (Sci)
A study of the antifriction properties of suspension solid-lubricating coatings based on molybdenum disulfide (MoS2) at high temperatures depending on the type of substrate, binder, additives, and load parameters was carried out. The solid lubricants were sprayed on two different substrates, high-temperature alloy (Inconel X-750) and stainless steel (AISI 430), tested under 10 N and 23 N loads at temperatures ranging from 25 °C to 800 °C. For comparison, different types of solid lubricants were used. In this work, it was established that the antifriction properties of solid lubricant suspension coatings at high temperatures significantly depend on the type of solid lubricant and the binder used. Moreover, it was shown that the use of Inconel X-750 as a substrate can lead to an increase in the critical operating temperature of coatings containing MoS2, graphite, and titanate as solid lubricant, additive, and binder, respectively. For instance, at load 23 N, the operating temperature increased from 480 °C to 496 °C. On the other hand, the coating based on graphite, containing ceramic as an additive, and an inorganic binder showed the best performance in terms of a combination of properties (low coefficient of friction and longer operation with a coefficient of friction below 0.3 under increasing temperature) when it was applied on the Inconel X-750 substrate. In addition, it was established that the coefficient of friction of graphite-based coatings gradually increases as they lose their antifriction properties due to their failure, while the coatings based on molybdenum disulfide show the opposite behavior, where the coefficient of friction increases sharply when it loses its lubricating properties.